Primary diffuse large B-cell lymphoma of the central nervous system (case report and literature review) - K. A. Komratova; Yu. G. Abugova; S. S. Ozerov; D. S. Abramov; G. V. Tereshchenko; N. V. Myakova (Онкогематология, 2017)
The central nervous system (CNS) involvement in patients with non-Hodgkin’s lymphomas is not uncommon, especially in children with mature B-cells lymphomas, unlike the primary CNS lymphoma (PCNSL). PCNSL is a rare extranodal form of NHL that occurs only in the CNS – in the brain, spinal cord, meninges, in the eyes, and not extending beyond CNS. Its frequency in adults is 1–2 % of lymphomas and 5 % of all CNS tumors. Data on prevalence in childhood are not available, limited to some case reports. This article presents a literature review about PCNSL diagnosis and treatment and case report of such lymphoma with intraspinal lesion in 11 years old child.